Detection of Salmonella carriers among apparently healthy cafeteria food handlers in tertiary care centre Pokhara - Chaudhary, Sushil Kumar; Regmi, Sanjib Mani; Devkota, Sunita; Gautam, Gyanendra; Pradhan, Shanti; Nagila, Amar (Journal of Gandaki Medical College-Nepal, 2022)
Introduction: Foodborne illnesses are caused by consumption of contaminated foods. The risk of food getting contaminated depends largely on the health status of the food handlers, their personal hygiene, knowledge and practice of food hygiene. Hence, this study aimed to assess the proportion of Salmonella among food handlers working in the cafeteria of Gandaki Medical College Teaching Hospital, Pokhara, Nepal.Methods: An institutional based cross-sectional analytical study was conducted from March 2018 to February 2019. A structured questionnaire was used to collect the sociodemographic characteristics, the knowledge and the risk factors of the participants. A total of 62 stool samples were collected and processed according to the standard microbiological procedures. All the Salmonella isolates were identified by biochemical tests. Additionally, antimicrobial susceptibility tests were performed according to Clinical and Laboratory Standards Institute guidelines 2017, using Kirby-Baur disk diffusion method. Data were analyzed by Statistical Package for Social Service for window version 21.0. Descriptive statistics were computed and chi-square test was applied at 5% level of significance. P-value